Persepsi Kemudahan, Kebermanfaatan dan Kepatuhan Wajib Pajak Terhadap Penggunaan E-filling - Imelda Sinaga; Victoria Ari Palma Akadiati; Agnes Susana Merry Purwanti (Jurnal Pemberdayaan Ekonomi, 2022)
Purpose: of this study is to investigate the perception of convenience, the perception of usefulness, and taxpayer compliance with the use of e-filling in order to obtain variables that have a significant and insignificant effect. Method: uses primary data in the form of a questionnaire which is analyzed using multiple linear regression with a sample of teachers and employees of Yadika SMA/SMK Bandar Lampung. Results: showed that the perceived convenience variable had no significant effect, the perceived usefulness variable had a significant effect and, the taxpayer compliance variable has no significant effect on the use of e-filling. Limitations: of this study are that taxpayers still have difficulty in filling out e-filing, the use of "e-filing has not been able to provide information in the appropriate format required by taxpayers, and taxpayers have not been on time in submitting SPT through e-filling. Contribution: to the field of taxation is that the perception of convenience, usefulness and, taxpayer compliance with the use of e-filling so that the local tax office can make improvements and socialize e-filing in its territory.